HGG-45. Characterization of spinal diffuse midline gliomas, H3 K28M-mutant. (3rd June 2022) - Stegat, Lotte; Thomas, Christian; Schweizer, Leonille; Neyazi, Sina; Pohl, Lara; Frank, Stephan; Dorostkar, Mario M; Schüller, Ulrich; Wefers, Annika K
Abstract: Diffuse midline gliomas (DMGs) are malignant gliomas that arise in the midline structures of the central nervous system. Due to their aggressive and diffuse growth and a two-year survival rate of less than 10%, DMGs are assigned to CNS WHO grade 4. Depending on the localization, median age of patients is about 11‒20 years. Genetically, most tumors are defined by a K28M-mutation in one of the highly homologous genes encoding histone protein H3. Since DMGs most frequently occur in pons and thalamus, comparatively little is known about spinal DMGs. Therefore, we histologically, molecularly, and clinically characterized spinal DMGs and analyzed, in which aspects they differ from DMGs of other localizations. Our cohort currently consists of 25 spinal DMGs and 40 pontine/thalamic reference cases. Histological, immunohistochemical and molecular analyses (DNA methylation, DNA panel sequencing) were done from FFPE tissue. Spinal DMGs were histologically very heterogeneous, both regarding different areas of single tumors as well as in comparison to other spinal and reference cases. First cluster analyses of DNA methylation data indicated a separation into three main clusters enriched for pontine, thalamic or spinal cases. The cluster enriched for spinal cases contained many tumors from elderly patients. Overall, mean age of patients with spinal DMGs was 28 years. Patients were significantly older than those with pontine DMGs. 19/20 spinal DMGs were H3-3A K28M-mutant, while one tumor had an H3-2B mutation. 4/19 (21%) spinal DMGs had mutations in FGFR1, and 6/10 (60%) in NF1. Three tumors had KRAS or BRAF mutations. In summary, first analyses suggest slight histological differences of spinal DMGs compared to DMGs of other localizations. Preliminary cluster analyses of DNA methylation data showed an enrichment of clusters for different localizations. About one third of spinal DMGs had mutations in a gene associated with the MAPK-signaling pathway.